Synbiotic modulate the host immune response to Salmonella typhimurium infection in commercial and indigenous chicken - Mohamed S. Elsharkawy; Mohamed M. Abdelbaki; Mahmoud Madkour; Eman E. EL Shanawany; Mohamad M. Aboelenin; Qiao Wang; Qinghe Li; Guiping Zhao; Jie Wen (Italian Journal of Animal Science)
This study examined the effect of the synbiotic product (PoultryStar®me) on Fayoumi and Cobb chickens upon exposure to Salmonella typhimurium (ST) infection and compared the responses of Fayoumi and Cobb chickens to ST infection. Fayoumi and Cobb chicks were fed synbiotic 1 g/kg feed from the first day. At 21 days of age, the chicks were orally challenged with 3 × 1012 cfu ST. At 72 h post-infection (pi), Fayoumi chickens showed significantly lower bacterial loads in their livers than Cobb chickens (p < 0.0001). Furthermore, the synbiotic reduced the bacterial load in the liver of both chicken types (p < 0.001). Moreover, the synbiotic product positively affected the plasma lysozyme content (p < 0.001) in both chicken types. The plasma IL-6 levels increased in the ST-challenged groups (p = 0.0003); moreover, the synbiotic reduced IL-6 levels in each type of chicken. The plasma IgG content increased only in the ST-challenged groups (p < 0.001) compared with the other groups. During ST infection, the synbiotic significantly decreased the proinflammatory cytokines expression including IL-8, IL-1β and TNF-α (p < 0.01) along with the frequency of TLR4 and MYD88 (p < 0.01) genes in both liver and spleen. Furthermore, Fayoumi chickens exhibited lower expression of these genes compared to Cobb chickens. Additionally, we found a significant interaction between chicken type and treatments, suggesting that different types of chickens may respond to pathogens differently. These findings indicate that the synbiotic can effectively modulate the host immune response to ST infection across different chicken types, with Fayoumi chickens demonstrating greater resistance to ST infection than Cobb chickens.